learning fragility. a philosophical meditation upon an existential exception - bárcena, fernando (childhood & philosophy, 2012)
It is not the “easiness” to learn — the fact that we are used to do it — that justifies thinking in education, but the experience of its difficulty. This is the root of the argument I pretend to develop in this text. It is a reflection that has as supporting point human experience, not that of normality, but of exceptionality, understood as the experience of the fragile and vulnerable. First, because I believe that some discourses about education have inaugurated the impertinent and perverse gesture of introducing young people (children and adolescents) into our school’s classrooms to — closing the doors behind them — prevent them to get in the outside world, converting them in eternal minors; eternals learners; and in second place because philosophy seems incapable (getting ashamed of itself) in its aspirations, to say almost anything in front of those that show themselves as a voice in the edge of the talk. In front of a whole tradition which, in moral philosophy in political philosophy and in philosophy of education as well, has considered these issues (ethical experience, political action, and educational activity, respectively) from the experience of a certain normal order, or of a normalized order, the aim of this paper is, then, to think education as an experience of the “care of the self” and of the “care of the other”, that adopts as supporting and ethical recognizing point the vulnerable, what becomes other by accident.